Phosphodiesterase 10A (PDE10A) as a novel target to suppress β-catenin and RAS signaling in epithelial ovarian cancer - Rebecca M. Borneman; Elaine Gavin; Alla Musiyenko; Wito Richter; Kevin J. Lee; David K. Crossman; Joel F. Andrews; Annelise M. Wilhite; Steven McClellan; Ileana Aragon; Antonio B. Ward; Xi Chen; et al. (BMC, 2022)
Abstract A leading theory for ovarian carcinogenesis proposes that inflammation associated with incessant ovulation is a driver of oncogenesis. Consistent with this theory, nonsteroidal anti-inflammatory drugs (NSAIDs) exert promising chemopreventive activity for ovarian cancer. Unfortunately, toxicity is associated with long-term use of NSAIDs due to their cyclooxygenase (COX) inhibitory activity. Previous studies suggest the antineoplastic activity of NSAIDs is COX independent, and rather may be exerted through phosphodiesterase (PDE) inhibition. PDEs represent a unique chemopreventive target for ovarian cancer given that ovulation is regulated by cyclic nucleotide signaling. Here we evaluate PDE10A as a novel therapeutic target for ovarian cancer. Analysis of The Cancer Genome Atlas (TCGA) ovarian tumors revealed PDE10A overexpression was associated with significantly worse overall survival for patients. PDE10A expression also positively correlated with the upregulation of oncogenic and inflammatory signaling pathways. Using small molecule inhibitors, Pf-2545920 and a novel NSAID-derived PDE10A inhibitor, MCI-030, we show that PDE10A inhibition leads to decreased ovarian cancer cell growth and induces cell cycle arrest and apoptosis. We demonstrate these pro-apoptotic properties occur through PKA and PKG signaling by using specific inhibitors to block their activity. PDE10A genetic knockout in ovarian cancer cells through CRISP/Cas9 editing lead to decreased cell proliferation, colony formation, migration and invasion, and in vivo tumor growth. We also demonstrate that PDE10A inhibition leads to decreased Wnt-induced β-catenin nuclear translocation, as well as decreased EGF-mediated activation of RAS/MAPK and AKT pathways in ovarian cancer cells. These findings implicate PDE10A as novel target for ovarian cancer chemoprevention and treatment.